Hubungan Dukungan Keluarga terhadap Kesiapsiagaan Lansia dan Ibu Hamil dalam Menghadapi Bencana Erupsi Gunung Berapi - Devi Permatasari; Puput Risti Kusumaningrum; Cahyo Pramono; Ahmad Izzudin (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: Preparedness among vulnerable populations living on volcanic slopes faces serious challenges, given the high potential for disasters such as volcanic eruptions. Vulnerable groups, such as the elderly and pregnant women, often have limited mobility and access to information, which makes it more difficult for them to respond quickly in the event of a disaster. The impact on pregnant women and the elderly is more severe compared to other age groups. This is due to the limitations of both the elderly and pregnant women. This requires the preparedness of pregnant women and the elderly in dealing with disasters. Objectives: research to determine the relationship of family support to the preparedness of pregnant women and the elderly. Methods: The research is quantitative correlation. The population is all pregnant women and the elderly who live in Balerante village, totaling 35 people. The sampling technique is total sampling with Kendall Tau analysis. Results: The majority of mothers aged 20-35 years were 95%, high school education as many as 10 respondents (67%), multigravida as many as 8 respondents (54%) and had no complications as many as 14 respondents (93%). The results showed that the family support of pregnant women was mostly good as many as 8 respondents (53%), and the majority in the elderly family support was good as many as 12 respondents (60%). The majority of pregnant women's good preparedness is in the moderately prepared category, namely 9 respondents (60%) and the majority in the elderly with the Ready category, namely a total of 12 respondents (40%). The results of the p value = 0.001 for pregnant women and for the elderly the p value = 0.009. Conclusions: Family support plays an important role in the preparedness of vulnerable groups, as families can provide emotional support, information, and resources needed to prepare for volcanic eruptions.